Một số đặc trưng địa chấn của đới đứt gãy Sông Hồng - Xuyên, Nguyễn Đình; Hùng, Phạm Quang; Nguyên, Phạm Đình; Sơn, Lê Tử; Thành, Trần Thị Mỹ (Vietnam Journal of Earth Sciences, 2000)
Some seismic characteristics of the Red River fault zone...